KATEKIS DALAM PERUTUSAN GEREJA DI TENGAH TUNTUTAN PROFESIONAL - Albert I Ketut Deni Wijaya (Lembaga Penelitian STKIP Widya Yuwana, 2019)
A catechist can be called a missionary and saint. This call is very appropriate considering their role in the missionary work of the Church. This research will answer two questions: (1) What is the role of catechists in the missionary work of the Church? (2) What is the professional catechism model in the midst of the needs of the world today? This study uses a qualitative method of literature study. Through this paper, it will be explained that in the mission of the Church, the catechist acts as a spokesman for the Christian congregation, a prophet, an educator and a witness. Where as the professional catechists needed are catechists who always present the Holy Spirit as their soul and missionary spirit while equipping themselves with skills and knowledge.